2020
DOI: 10.1088/1757-899x/879/1/012136
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System for Public Transportation Selection

Abstract: The purpose of this research is to give an advice related to the transportation inspection by using a decision support system. Literature study, observation, system design, and system testing were used as methods in this research. With this method, we can create a system that can support the decision of the rhamp check officer to determine the proper transportation to operate. The result of this research is obtaining the data about the criteria used as a reference in making decisions about the feasibility of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Kazak's research found the high usefulness of the analyzed decision support system to solve the problem of public transport design [20]. Soegoto gave advice related to the transportation inspection by using a decision support system [21].…”
Section: Introductionmentioning
confidence: 99%
“…Kazak's research found the high usefulness of the analyzed decision support system to solve the problem of public transport design [20]. Soegoto gave advice related to the transportation inspection by using a decision support system [21].…”
Section: Introductionmentioning
confidence: 99%